New Conjugacy Coefficient for Conjugate Gradient Method for Unconstrained Optimization - Hamsa Chilmeran; Huda Najm (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper, we derived a new conjugacy coefficient of conjugate gradient method which is based on non-linear function using inexact line searches. This method satisfied sufficient descent condition and the converges globally is provided. The numerical results indicate that the new approach yields very effective depending on number of iterations and number of functions evaluation .